Kepuasan Pasien Terhadap Layanan Rawat Inap RSUD Jagakarsa Tahun 2017/2018 - Mustika, Dewi (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
Service Quality is very important in creating patient satisfaction. This study aims to determine the criteria of patients on hall of residence services, the relationship of dimensions of service quality with patient satisfaction and to determine which dimensions have the most influence on patient satisfaction. This study carried out univariate, bivariate and multivariate analyzes. With a total sample of 150 respondents. It was found that the characteristics of patients for the age with the highest category were in the range of 30-49 years, namely 54%, the sex of the most respondents was 78%, the history of the highest education was SMA 53.3%, the work of the most respondents was IRT, the highest frequency of income was income per month Rp.3,000,000 to Rp. 4,000,000. For bivariate analysis it was found that from the five dimensions of four-dimensional service quality had a significant effect on patient satisfaction: reliability (p value 0.001), responsiveness (p value < 0.0001), emphaty (p value < 0.0001) and tangible (p value < 0.0001). And the multivariate analysis found that the dimensions of reliability and empathic affect patient satisfaction